Analysis Layout in Supermarket between AVIA and Souvernir-Center Haikou - Steve Anderson Singgih; Vincent Hendrawan (Journal of International Conference Proceedings (JICP), 2018)
Layout should be considered in the field of business, the application of a good layout system, there are many benefits and influence on consumers.For example in Haikou, China. There is a center of souvenirbased coconut. The self-applied Lay Out is very unique and rarely used by the Gift Souvenir Center in Indonesia. They set the layout of the free flow pattern but made like a snake path, so consumers would not want to follow the path so that consumers also indirectly see their other products of various kinds. It is very good to attract the attention of consumers and there are products that are discounted again but placed in different places when the product is the same as the one placed at the beginning. Result : Layout determine revenue Keywords: Layout, Souvenir-Center, Business